Etiologies of zygomatic bone fracture at a tertiary care hospital of South Punjab, Pakistan - Khan, Usman Qadir; Shaikh, Qaimuddin; Rana, Zahoor Ahmed; Shabnum, Shazia; Ambreen, Nadia; Nazir, Saadia (International Journal of Research in Medical Sciences, 2020)
Background: Fracture of the zygomatic bone is a frequent maxillofacial trauma, due to its distinction which influences it to bear the brunt of facial trauma but its pattern seems to vary geographically. This study was planned to find out etiologies of zygomatic bone fracture at a tertiary care hospital of South Punjab, Pakistan. Methods: This descriptive observational study was conducted at The Department of Oral and Dental Surgery, Shaikh zayed Medical College Hospital Rahim Yar Khan, Pakistan, from July December 2017. A total of 114 patients with isolated tripod zygomatic bone fracture were enrolled. Demographic characteristics of the patients along with etiologies of zygomatic bone fracture were recorded. Results: Out of a total of 114 patients having zygomatic bone fractures, there were 85 (74.6%) male. Majority of the patients, 58 (50.9%) were aged between 21 to 30 years, 78 (68.4%) belonged to rural areas, 42 (36.8%) laborers while socio-economic class of 66 (57.9%) patients was recorded to be middle income. Road traffic accidents were the commonest, seen among 48 (42.1%) patients followed by inter-personal violence and falls, noted among 26 (22.8%) and 17 (14.9%) patients respectively. Conclusions: Zygomatic bone fractures were most commonly seen among male gender and young age groups. Road traffic accidents and inter-personal violence were the most commonly noted etiologies in the present study.